The Influence of Project-Based Learning (PjBL) Model on Students' Learning Motivation and Critical Thinking Skills in Ecological Area Development Material - Mar'atus Sholihah; Sukma Perdana Prasetya; Muzayanah (Universitas Pendidikan Ganesha, 2025)
This study is motivated by the low learning motivation of students in the topic of Ecological Region Development, indicating that the instructional process has not yet succeeded in fostering active engagement and student interest. In addition, students’ critical thinking skills remain suboptimal, as reflected in their limited ability to analyze, evaluate, and solve problems related to ecological issues. This study aims to examine the effect of Project-Based Learning (PjBL) on students’ learning motivation and critical thinking skills in the subject of Ecological Regional Development. A quantitative approach was employed using a quasi-experimental nonequivalent control group design involving two Grade XII classes, designated as the experimental group (PjBL) and the control group (conventional instruction). The research instruments consisted of a learning motivation questionnaire based on Keller’s ARCS model and a critical thinking test constructed using Facione’s framework. The findings indicate a significant increase in learning motivation, from an average score of 68.20 to 82.50, as well as an improvement in critical thinking skills, from 57.18 to 80.75. Independent t-tests further revealed significant differences between the two groups. The study concludes that the PjBL model is effective in enhancing students’ motivation and critical thinking skills, as it provides contextual, collaborative, and real-world problem-solving learning experiences.